Pemberdayaan Perekonomian Dan Analisa Usaha Melalui Pembuatan Tepung Mocaf Di Kecamatan Siak Hulu Pekanbaru - Sri Maryanti; Rita Wiyati; Muhammad Thamrin (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2018)
Cassava cultivation in Siak Hulu District Kampar Riau of Province sold more in the form of primary goods or just processed into tape, opak and traditional cakes that have less economic value. This is because the lack of knowledge of farmers related to other processed cassava is one of them Flour Mocaf which has a function similar to wheat flour, rice and other flour, this flour has a huge market potential so it is very likely to be developed among farmers . So the level of dependence on wheat can be reduced, considering flour is imported products. The method used for making mocaf flour is cassava peeled, washed to mucil on cassava is lost and cut small then soak in drum that contains water for 3 days or 72 hours ago dried and finely ground and packed. If analyzed making mocaf flour is very likely for new farmers or entrepreneurs to start their business with greater profit, especially if processed products made from mocaf flour can be produced variously will certainly bring in greater profit. This means that after this activity, more farmers know the other benefits of cassava which has added value higher. Cassava can be processed into substitution products from wheat by way of processing cassava into mocaf flour through a very simple process so easily understood by farmers who have different educational background.